Mediação algorítmica como uma das facetas da mediação da informação - Rangel, Tayná Ladislau (2024)
Algorithmic mediation is a process of intermediation between users and information available in digital environments, carried out through algorithms, with a direct connection to information mediation by facilitating users' access, use, and appropriation of information. Seeking to understand this relationship, this study aims to analyze how algorithms have contributed to directing information mediation in the digital environment, with specific objectives: examining the algorithmic perspective from Information Science; discussing the concept of Algorithmic Mediation and its informational diversity; understanding how algorithms act as information mediators; tracing the timelines of algorithms and their impacts on information mediation. The theoretical framework was based on bibliographic research, aiming to establish dialogues and relationships between the Social Sciences, Computer Science, Communication, and Information Science (IS). The research is exploratory, aiming to provide greater familiarity with the problem, considering it is a topic still little studied in IS. The methodology used in this research is based on a correlational approach, which evaluates the degree of association between two or more variables, allowing observation of the forms and use of algorithmic mediation, as well as tracing the timelines of each information mediation development process and algorithm development. This research is descriptive in nature, with a qualitative approach. Data analysis aimed to establish complementary relationships between different fields of knowledge to understand how information mediation has been impacted by algorithmization. It is found that algorithmic mediation emerges as an important facet in contemporary society, critically analyzing algorithms and their ethical and social implications. It is concluded that algorithms exert direct influence on the production, dissemination, and consumption of information, requiring an interdisciplinary approach to address the challenges arising from their application in society.